Impact of eNOS 27-bp VNTR (4b/a) gene polymorphism with the risk of Systemic Lupus Erythematosus in south Indian subjects - Katkam, Shiva Krishna; Indumathi, Bobbala; Tasneem, Fatima S.D.; Rajasekhar, Liza; Kutala, Vijay Kumar (Gene, 2018)
Endothelial nitric oxide synthase (eNOS) is constitutively expressed by vascular endothelium including glomerular endothelium. Functional polymorphisms, -786T>C (rs2070744) promoter variant, 27 bp VNTR (4b/a) in intron 4 and 894G>T (rs1799983) exon variant of eNOS are known to alter the eNOS expression and activity leading to altered NO levels and contribute to the development of vascular and renal disease risk. Thus it might have a role in SLE risk and development of glomerulonephritis. Hence, the present study is aimed to investigate the role of eNOS polymorphisms in South Indian SLE patients. Five hundred and four subjects (219 SLE cases and 285 controls) were included in the present case-control study. Genotyping was done using polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) for -786T>C and 894G>T SNPs. Another, 4a4b variable number of tandem repeat polymorphism was genotyped using direct PCR method using primer pairs flanking the 27 bp direct repeat region in intron 4 of eNOS gene. Our analysis revealed that intron 4 27 bp VNTR genotype frequency differ significantly between the SLE patients and controls (OR: 1.73, 95% CI %:1.18–2.54, P = 0.004). Further, “a allele” frequency was significantly higher in SLE patients as compared to the controls (20 vs. 13.8%) (OR: 1.56, 95%CI: 1.11–2.18, P = 0.01). However, promoter polymorphism −786T>C and missense variant 894G>T were not significantly different between the SLE cases and controls (OR: 0.92, 95%CI: 0.64–1.33, P = 0.7 and OR: 1.4, 95%CI: 0.95–2.06, P = 0.095 respectively). Furthermore, no association was found between any of the three polymorphisms with lupus nephritis phenotype. Increased plasma nitrate levels were observed in SLE patients (36.79 ± 2.83 μM/L) as compared to healthy controls (28.53 ± 1.94 μM/L) (P = 0.01). In addition, the genotype-based simulations have indicated that combined effect of eNOS polymorphisms contribute to 30.5% variability in NO production. Results of the present study indicate that 27-bp VNTR polymorphism in intron 4 of eNOS gene polymorphism may be the significant risk factor for SLE in south Indian subjects. •Significant association was found between the 27-bp VNTR (4b/a)polymorphism and SLE.•Haplotype analysis revealed “TaG” as risk haplotype for SLE.•Significant increase in plasma NO levels in SLE patients compared to control group.•Combined effect of eNOS polymorphisms contributing to 30.5% variability in NO production.•Subjects with 894GT/786TT/ba and 894GT/786TT/aa genotypes have lowest NO bioavailability.